The Mitochondria-Targeted Antioxidant SkQ1 Downregulates Aryl Hydrocarbon Receptor-Dependent Genes in the Retina of OXYS Rats with AMD-Like Retinopathy - M. L. Perepechaeva; A. Yu. Grishanova; E. A. Rudnitskaya; N. G. Kolosova (Journal of Ophthalmology)
The mitochondria-targeted antioxidant SkQ1 is a novel drug thought to retard development of age-related diseases. It has been shown that SkQ1 reduces clinical signs of retinopathy in senescence-accelerated OXYS rats, which are a known animal model of human age-related macular degeneration (AMD). The aim of this work was to test whether SkQ1 affects transcriptional activity of AhR (aryl hydrocarbon receptor) and Nrf2 (nuclear factor erythroid 2-related factor 2), which are considered as AMD-associated genes in the retina of OXYS and Wistar rats. Our results showed that only AhR and AhR-dependent genes were sensitive to SkQ1. Dietary supplementation with SkQ1 decreased the AhR mRNA level in both OXYS and Wistar rats. At baseline, the retinal Cyp1a1 mRNA level was lower in OXYS rats. SkQ1 supplementation decreased the Cyp1a1 mRNA level in Wistar rats, but this level remained unchanged in OXYS rats. Baseline Cyp1a2 and Cyp1b1 mRNA expression was stronger in OXYS than in Wistar rats. In the OXYS strain, Cyp1a2 and Cyp1b1 mRNA levels decreased as a result of SkQ1 supplementation. These data suggest that the Cyp1a2 and Cyp1b1 enzymes are involved in the pathogenesis of AMD-like retinopathy of OXYS rats and are possible therapeutic targets of SkQ1.